2016
DOI: 10.1007/s13592-016-0454-6
|View full text |Cite
|
Sign up to set email alerts
|

Different but the same: bumblebee species collect pollen of different plant sources but similar amino acid profiles

Abstract: -Access to abundant and diverse floral plant sources is essential for generalist bees as they obtain all energy and nutrients required from pollen and nectar. Despite their importance, we still know little about the precise nutritional requirements of most bee species. Here, we investigated differences in floral and amino acid profiles of pollen collected by five bumblebee species in southern Germany, which had access to the same spectrum of plant species and thus sources of nutrition. We found that different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 52 publications
2
67
0
1
Order By: Relevance
“…Moreover, the impact of pollen nutrients (e.g. In previous work, the role played by amino acids content on bumblebee colony growth and foraging behaviour was underlined Kriesell et al, 2016). In previous work, the role played by amino acids content on bumblebee colony growth and foraging behaviour was underlined Kriesell et al, 2016).…”
Section: Mixed Pollen Diet and Nutrient Content Of Pollenmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the impact of pollen nutrients (e.g. In previous work, the role played by amino acids content on bumblebee colony growth and foraging behaviour was underlined Kriesell et al, 2016). In previous work, the role played by amino acids content on bumblebee colony growth and foraging behaviour was underlined Kriesell et al, 2016).…”
Section: Mixed Pollen Diet and Nutrient Content Of Pollenmentioning
confidence: 99%
“…Although different studies have shown that bumblebees tend to forage on resources with high amino acid content (Leonhardt & Bl€ uthgen, 2012;Somme et al, 2015;Kriesell et al, 2016), the main foraged resource in the Upper Ardennes (i.e. Although different studies have shown that bumblebees tend to forage on resources with high amino acid content (Leonhardt & Bl€ uthgen, 2012;Somme et al, 2015;Kriesell et al, 2016), the main foraged resource in the Upper Ardennes (i.e.…”
Section: Diet Quality and Floral Choices Of Bumblebeesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the nutritional quality of pollen and in particular its protein content seems to largely determine bumblebee colony development (K€ amper et al 2016;Moerman et al 2017;Roger et al 2017) as well as bumblebee immune defence (Di Pasquale et al 2013;Brunner et al 2014;Roger et al 2017). Pollen protein content and amino acid profiles furthermore correlate with foraging preferences (Kitaoka & Nieh 2009;Leonhardt & Bl€ uthgen 2012;Kriesell et al 2017). However, more recent studies suggest that, in addition to protein, fat also plays an important role in nutrient regulation for bumblebees (Vaudo et al 2016a;Vaudo et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…As different bee species display specific nutritional requirements (e.g. sterol compounds), they could show variation that may influence their host-plant foraging patterns [25, 39, 40]. As far as we know, the study of such interspecific variability in nutritional requirements and, in turn, host-plants resource resources quality remains lacking for bumblebee species.…”
Section: Introductionmentioning
confidence: 99%